RESILIENCE OF ADOLESCENT POST-DISASTER ERUPTION OF MOUNT SEMERU: LITERATURE REVIEW - Primasari Mahardhika Rahmawati; Suhari Suhari; Anggia Astuti; Musviro Musviro (Journal of Vocational Nursing)
Introduction